Case study of the export of the regional cinema model in Africa - Mejías Martínez, Guillermo (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2022)
In the post-COVID19 era, a new paradigm shift in the film market has become evident. The regional film model has been relegated to very specific circles, but with the current situation this could change. The aim of this paper is to study the Ugandan regional action film model, known as "Wakaliwood", together with a case in Spain whose proposal shares a similar approach to that used by Wakaliwood. The results indicate that a new iteration of the regional film model versus the classical production model can be successfully exported to the international market.